Workers' sleep condition and related disorders in Japan: an analysis based on health insurance claim data and questionnaire. Issue 4 (2nd October 2018) - Toyoshima, Ayako; Moriyama, Michiko; Asano, Kenichiro; Mitsuhashi, Keiko; Rahman, Md Moshiur
Abstract : The purpose of this study was to clarify the sleep disorders and sleep conditions among workers in a company through descriptive statistics. We analyzed the data of individuals with suspected sleep disorders based on the 1-year outpatient health insurance claim data of 2803 employees in a company in Japan. We conducted a questionnaire survey to determine the sleep condition and drug usage of the same participants. Claim data of 339 employees (12.1%) were selected for analysis, and the breakdown of diseases comprised 153 (5.5%) with sleep disorders, 149 (5.3%) with headache, 119 (4.2%) with depression and 17 (0.6%) with autonomic imbalance. We recovered 2608 questionnaire responses (93.0%) and found that 1852 subjects (71.0%) were aware of insomnia symptoms within 1 year. Our findings highlight the prevalence of sleep disorders and drug usage among workers in a company, and the conditions of these disorders, including awareness of insomnia.